Diseño de un plan de marketing de servicios para la Empresa Licorjadiom comercializadora de licores ubicada en la ciudad de Quito - Sigcho Goyes, Mario Javier (2014)
The company LICORJADIOM there about 3 years ago, it is dedicated to the marketing of spirits to restaurants, bars, clubs and the general public. The company has had several opportunities for growth, since every day there are several fun sites, which demand such products. In order to minimize the problems that the company is necessary to design a marketing plan services, which provide tolos to increase sales of their products, positioning the brand in the market and meet the needs of customers, to create loyalty.